2018
DOI: 10.3329/baj.v21i1.39360
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Performance of Foxtail Millets Under Salinity

Abstract: Crop diversification in saline affected coastal areas is crucial for food security in Bangladesh. A pot experiment was conducted at polythene house at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur-1706 during May to August, 2017 to determine the effect of salt stress on growth and yield performance of foxtail millets. Five foxtail millets genotypes viz. (i) BARI Kaon-1 (check), (ii) BD-878, (iii) BD-897, (iv) BD-891 and (v) BD-881 were tested under three salt stresses viz. (i) control (0 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“… Finger Millet Drought induced oxidative stress in finger millet by trehalose and methyl jasmonate was modulated Pearl millet Attempt was made to maintain pearl millet germplasm Population development of pearl millet Foxtail millet In Bangladesh's saline-affected (6 dS/m) coastal regions, foxtail millets genotypes BD-897 and BD-881 may be grown. [ 40 ] Mutagenesis was induced in foxtail millet to develop variable population [ 40 ] Maintenance and seed increase of foxtail millet germplasm Proso millet Due to the low cost, accessibility of their seeds, low danger, low water demand, and ease of cultivation without the use of contemporary technology, all proso millet kinds and cultivars may be produced in char land. [ 41 ] Maintenance of proso millet germplasm [ 39 ] Potential proso millet lines were verified in a rainfed environment …”
Section: Challenges Of Millets Cultivation In Bangladeshmentioning
confidence: 99%
“… Finger Millet Drought induced oxidative stress in finger millet by trehalose and methyl jasmonate was modulated Pearl millet Attempt was made to maintain pearl millet germplasm Population development of pearl millet Foxtail millet In Bangladesh's saline-affected (6 dS/m) coastal regions, foxtail millets genotypes BD-897 and BD-881 may be grown. [ 40 ] Mutagenesis was induced in foxtail millet to develop variable population [ 40 ] Maintenance and seed increase of foxtail millet germplasm Proso millet Due to the low cost, accessibility of their seeds, low danger, low water demand, and ease of cultivation without the use of contemporary technology, all proso millet kinds and cultivars may be produced in char land. [ 41 ] Maintenance of proso millet germplasm [ 39 ] Potential proso millet lines were verified in a rainfed environment …”
Section: Challenges Of Millets Cultivation In Bangladeshmentioning
confidence: 99%
“…The NaCl concentration of 75 mM was expected to simulate moderate salinity stress. Foxtail millet was reported to have good salinity tolerance in the moderate range (4-8 dS.m -1 ) (Nahar et al 2018;Mushtaq et al 2021). Each experimental unit comprises eight polypots (1.7 L) containing a media mixture of soil and sand (1:1, v/v), with one seedling per polypot.…”
Section: Salinity Tolerance Evaluation At Seedling Stagementioning
confidence: 99%
“…Foxtail millet has also been reported to show comparable tolerance to salinity (Ardie et al 2015;Akter et al 2020) and drought (Xiao et al 2021) stresses, indicating the adaptive nature of the species to adverse environmental conditions. Nahar et al (2018) reported that salttolerant foxtail millet accession could maintain its dry matter and grain yield at the salinity level of 6 dS.m -1 , while Krishnamurthy et al (2014) evaluated 155 foxtail millet accessions under soil saturated with 100 mM NaCl and identified 13 highly tolerant foxtail millet accessions. The salt tolerance potential of foxtail millet is associated with its efficient energy production under stress (Han et al 2022).…”
mentioning
confidence: 99%
“…Foxtail millet has a great potential for salt tolerance due to its strong fibrous root system, high water utilization rate, strong drought tolerance, and salt tolerance potential [ 14 , 15 ]. Nahar et al [ 16 ] found that the salt tolerance of a foxtail millet accession could maintain higher dry matter and grain yield at 6 dS·m −1 salt level. Krishnamurthy et al [ 17 ] identified 155 foxtail millet accessions in India on soil saturated with 100 mM NaCl, of which 13 accessions were highly tolerant.…”
Section: Introductionmentioning
confidence: 99%